LIMITATIONS OF VITAL ACTIVITY IN CHILDREN WITH DISABILITIES DUE TO HEARING DISORDERS - Горяйнов, Игорь Владимирович; Владимирова, Оксана Николаевна; Шабанова, Оксана Антоновна (Medicine in Kuzbass, 2018)
The data on 611 children with disabilities due to ear and mastoid diseases, which were examined in theFederal Governmental Institution «Main Bureau of Medical and Social Expertise in St. Petersburg» – the Bureau of the medical and social expertise of the pediatric profile for 2015-2016 are analyzed. Identified the main limitations of life, expert-significant domains of the international classification of functioning (ICF) have been studied. The carried out research allows to form modern approaches to expert-rehabilitation diagnostics of life limitations in disabled children due to ear diseases and mastoid process taking into account the international classification of functioning provisions.